Identification of Factors Affecting Smoking Prevalence in West Java using Spatial Modeling: Identifikasi Faktor-Faktor Yang Memengaruhi Prevalensi Merokok di Jawa Barat Menggunakan Pemodelan Spasial - Baktiar, Aditya Firman; Utiayarsih, Toza Sathia (Statistics and Data Science Program Study, SSMI, IPB University, in collaboration with the Forum Pendidikan Tinggi Statistika Indonesia (FORSTAT) and the Ikatan Statistisi Indonesia (ISI), 2022)
Smoking behavior is certainly a serious problem that needs to be resolved immediately in Indonesia. It because smoking has been shown to trigger various diseases. More than that, smoking can also causes death. Based on the results of Riskesdas in 2013 and 2018, the province with the highest smoking prevalence in Indonesia is Jawa Barat. Moreover, the prevalence of smoking in Jawa Barat also shows a stable trend and has always been above the national prevalence since 2001. If we look at the spatial distribution, the prevalence of smoking in Jawa Barat shows a grouping where close districts/cities have a similar values to each other. It indicates spatial dependencies that need to be accommodated in the modeling. Therefore, this study was conducted to determine the factors that influence the prevalence of smoking in Jawa Barat by using spatial analysis. Based on the spatial lag model, it was found that the percentage of the population graduating from high school and the percentage of the highland area had a significant effect on smoking prevalence in Jawa Barat. While the percentage of the married population, the percentage of the working population, and tobacco production had no significant effect.